Noninvasive genetic testing for type IV collagen nephropathy using oral mucosa DNA sampling in children with haematuria - Jiaojiao Liu; Dayin Zhou; Xiaowen Wang; Tong Shen; Chunyan Wang; Rufeng Dai; Xinli Han; Lin Huang; Wenli Xu; Jing Chen; Yihui Zhai; Jia Rao; et al. (Renal Failure)
Objective Hematuria is one of the most common conditions in children, and increase the risk of chronic kidney disease. Persistent hematuria may be the earliest manifestation of type IV collagen-related nephropathy. Early diagnosis is essential for optimized therapy. Due to the invasive nature of kidney biopsy and the high cost of whole exome sequencing, its application in the diagnosis of isolated hematuria is rare. Hence, we performed noninvasive and convenient genetic testing approaches for type IV collagen-related nephropathy.Methods We used noninvasive oral mucosa sampling as an alternative method for DNA isolation for genetic testing and designed a panel targeting three type IV collagen nephropathy-related genes in children with hematuria. Children with persistent hematuria unaccompanied by clinically significant proteinuria or renal insufficiency who underwent genetic testing using a hematuria panel were enrolled.Results Thirty-seven of 112 (33.0%) patients were found to have a genetic variant in COL4A3/A4/A5. Pathogenic/likely pathogenic COL4A3/A4/A5 variants were identified in 17 of the 112 patients analyzed (15.2%), which were considered to explain their hematuria manifestations. In addition, variants of unknown significance (VUSs) were found in 17.8% (20/112) of patients. Furthermore, we observed a much greater COL4A3/A4/A5 variant detection rate in patients with a positive family history or more severe hematuria (RBC ≥ 20/HP) or with coexisting microalbuminuria (59.2% vs. 12.7%, p < 0.001; 64.0% vs. 24.1%, p < 0.001; 66.7% vs. 30.1%, p = 0.025).Conclusions We present the high prevalence of variants in COL4A genes in a multicenter pediatric cohort with hematuria, which requires close monitoring and long-term follow-up.